A case study : construction of bucket foundations for jackup ships - Qiu, Gang; Hamann, Thorben; Grabe, Jürgen; Hein, Christian; Howe, Robert (Volume 6: Polar and Arctic Sciences and Technology; Offshore Geotechnics; Petroleum Technology Symposium, 2013)
Jackup ships are built to transport wind turbines foundation between offshore logistics center and the installation site. It require sufficiently stable seabed next to quay walls. Otherwise jackup processes may reduce the stability of the quay wall and remained footprints of the legs could induce unsafe jackup procedures in the future. Foundations have been planned to improve the strength of seabed in front of the quay wall. The numerical analyses of the penetration/extraction processes of the legs into/out of the foundations were presented in OMAE2011-49928 to study the bearing capacity of two foundation designs (open-ended cylinder and bucket foundation). In consequence of the numerical studies, the bucket foundation was selected and was improved by reduction the height of the foundations and adjust the inclination of the inner wall to reduce the construction costs. Four bucket foundations have been built in Bremerhaven, Germany. This paper provided of a resume of design, construction and set-up process. The penetration and extraction processes of the jackup legs were tested the results were compared with the numerical predictions.